Novel bio-functional Aloe vera beverages fermented by probiotic Enterococcus faecium and Lactobacillus lactis - Cuvas, Ruth (2022)
Aloe vera has been medicinally used for centuries. Its bioactive compounds have been shown to be very effective in the treatment of numerous diseases. In this work, a novel functional beverage was developed and characterized to combine the health benefits of probiotic bacteria with the Aloe vera plant itself. Two Aloe vera juices were obtained by fermentation either by a novel isolated Enterococcus faecium or a commercial Lactococcus lactis. The extraction of Aloe vera biocompounds for further fermentation was optimized. Extraction with water plus cellulase enhanced the carbohydrates and phenolic compounds in the obtained extracts. The biotransformation of the bioactive compounds from the extracts during fermentation was assessed. Both probiotic bacteria were able to grow on the Aloe vera extract. Lactic acid and short-chain fatty acids (SCFA) together with fourteen individual phenolic compounds were quantified in the produced Aloe vera juice, mainly epicatechin, aloin, ellagic acid, and hesperidin. The amount of total phenolic compounds was maintained through fermentation. The antioxidant activity was significantly increased in the produced juice by the ABTS method. The novel produced Aloe vera juice showed great potential as a functional beverage containing probiotics, prebiotics, SCFA, and phenolic compounds in its final composition.